2015
DOI: 10.5713/ajas.15.0166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Candida norvegensis</i> Live Cells on <i>In vitro</i> Oat Straw Rumen Fermentation

Abstract: This study evaluated the effect of Candida norvegensis (C. norvegensis) viable yeast culture on in vitro ruminal fermentation of oat straw. Ruminal fluid was mixed with buffer solution (1:2) and anaerobically incubated with or without yeast at 39°C for 0, 4, 8, 16, and 24 h. A fully randomized design was used. There was a decrease in lactic acid (quadratic, p = 0.01), pH, (quadratic, p = 0.02), and yeasts counts (linear, p<0.01) across fermentation times. However, in vitro dry matter disappearance (IVDMD) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
4
11
0
Order By: Relevance
“…Due to this, Levazot 15 is considered the most promising yeast strain to be used as a microbial additive to improve digestive fermentation of ruminants fed fibrous diets. The higher gas production level obtained with this strain is probably due to an increase in propionic acid synthesis, 35 which facilitates the formation of carbon dioxide (CO 2 ) via the succinate–propionate metabolic pathway. 36 In vivo and in vitro studies have shown increased rates of cellulose and NDF degradation in the presence of yeasts, 37 , 38 which could explain the increase in the gas production level found in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Due to this, Levazot 15 is considered the most promising yeast strain to be used as a microbial additive to improve digestive fermentation of ruminants fed fibrous diets. The higher gas production level obtained with this strain is probably due to an increase in propionic acid synthesis, 35 which facilitates the formation of carbon dioxide (CO 2 ) via the succinate–propionate metabolic pathway. 36 In vivo and in vitro studies have shown increased rates of cellulose and NDF degradation in the presence of yeasts, 37 , 38 which could explain the increase in the gas production level found in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these results, the Levazoot 15 yeast strain could be potentially used as an additive for ruminants consuming high-fiber diets. In another study, Ruiz et al [38] showed that the same strain of yeast did not affect the ruminal cellulolytic bacterial counts. However, the treatment with yeast cultures positively influenced the cellulolytic fungal populations in rumen after 4 h of incubation.…”
Section: Other Non-saccharomyces Strains Of Yeasts With Potential Commentioning
confidence: 95%
“…We performed two experimental designs based on in vitro ruminal fermentation tests. Regarding the debate between in vitro and in vivo tests, it is worth highlighting that there is a consensus of several experts (Yáñez- Ruiz et al, 2016;Danielsson et al, 2017) in that IVtFT is very useful for screening diets and preliminary evaluation of feed additives and inhibitory agents of CH 4 production in ruminal fermentation. They also advise running IVvFT after the IVtFT to confirm the main results as well as to gain more information that can only be obtained in IVvFT, before making decisions or implementing strategies at the commercial level.…”
Section: Experimental Designmentioning
confidence: 99%
“…Instead of using Lv or other specific chemical inhibitors, a promising avenue for ruminal CH 4 mitigation is the use of cultures (for instance, yeast cultures) as an inhibitor of CH 4 production in ruminal fermentation. In the work of Ruiz et al (2016), the authors studied the effects of the supplementation of Candida norvegensis (Cn) (live cells and likely metabolites present in the used medium) on the ruminal fermentation of oat straw (as the sole source of carbon, no actual cattle ration was used). Their results hold promise for developing an original approach to mitigation of ruminal CH 4 generation.…”
Section: Effect Of Lovastatin Concentration On Total Gas Production Ch 4 Hydrogen and Short-chain Fatty Acidsmentioning
confidence: 99%